2007
DOI: 10.1007/s10384-007-0480-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Epithelial Defects Due to Neurotrophic Keratopathy Treated with a Substance P-Derived Peptide and Insulin-Like Growth Factor 1

Abstract: Eye drops containing FGLM-amide and IGF-1 induced the rapid resurfacing of persistent epithelial defects in individuals with neurotrophic keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 16 publications
1
46
0
2
Order By: Relevance
“…Effective treatment of PED has been described with eye drops containing fibronectin [31], autologous serum [32][33][34][35], substance P plus IGF-1 [14,[36][37][38], and nerve growth factor [39] as well as thymosin beta 4 [40,41]. Our present epidemiological study suggests that an optimal therapeutic approach may assist both in restoring the scaffold or underlying substrate for corneal epithelial cells with agents such as fibronectin, hyaluronic acid, and autologous serum, and in enhancing the physiological functions of corneal epithelial cells with agents such as nerve growth factor, epidermal growth factor, and substance P plus IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Effective treatment of PED has been described with eye drops containing fibronectin [31], autologous serum [32][33][34][35], substance P plus IGF-1 [14,[36][37][38], and nerve growth factor [39] as well as thymosin beta 4 [40,41]. Our present epidemiological study suggests that an optimal therapeutic approach may assist both in restoring the scaffold or underlying substrate for corneal epithelial cells with agents such as fibronectin, hyaluronic acid, and autologous serum, and in enhancing the physiological functions of corneal epithelial cells with agents such as nerve growth factor, epidermal growth factor, and substance P plus IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that FGLM-NH 2 + SSSR eyedrops [17] and PHSRN eyedrops [18] facilitated corneal epithelial migration in a rat model of diabetes. Furthermore, both types of eyedrops promoted corneal epithelial wound closure in patients with PEDs [12, 19, 20]. However, treatment of PEDs in diabetic patients with such peptide eyedrops is likely to be insufficient in the presence of other abnormalities of the cornea that impede epithelial migration in response to such drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have previously shown that eyedrops containing the substance P-derived peptide FGLM-NH 2 plus IGF-1 [17] or PHSRN [18] facilitated corneal epithelial wound closure in diabetic rats. In addition to the effectiveness of PHSRN eyedrops for the treatment of PEDs in patients with diabetic keratopathy [12], we also found that eyedrops containing FGLM-NH 2 and either IGF-1 [19] or the IGF-1-derived peptide SSSR [20] were effective for the treatment of PEDs in patients with neurotrophic keratopathy. Despite the potential of these various peptides for the treatment of PEDs associated with diabetic keratopathy, however, we encountered some cases that responded with incomplete epithelial resurfacing.…”
Section: Introductionmentioning
confidence: 94%
“…Patients or animals with PEDs associated with neurotrophic keratopathy have thus been treated successfully with eyedrops containing substance P or FGLM-amide as well as IGF-1 or SSSR. 12,13 The present study investigated whether the administration of eyedrops containing FGLMamide and SSSR is effective for the prevention of the SPK that develops after cataract surgery in diabetic patients.…”
mentioning
confidence: 99%